FREQUENCIES OF BLOOD GROUP ANTIGENS AND CORRESPONDING ALLELES IN THE POPULATION OF MIRPUR, AZAD JAMMU KASHMIR, PAKISTAN - M. Khalid; M. A. Qureshi (Journal of Animal and Plant Sciences, 2006)
A sample of 3927 subjects was collected from the Mirpur, Azad Jammu Kashmir, Pakistan. A frequency distribution of 26.38%, 32.50%, 9.47% and 31.65% was observed for blood groups A, B, AB and O, respectively, while 91.04% of the subjects being Rh positive. The allelic frequencies were calculated to be 0.2, 0.238 and 0.562 for A, B and O alleles, respectively, and 0.299 for d allele. The data did not show significant differences between males and females during the study period with respect to allelic frequencies of blood groups and was found to be in Hardy-Weinberg equilibrium. The trend of blood groups and allelic frequencies has been compared with other regions of Pakistan.
Keywords: Mirpur; Azad Jammu Kashmir; Pakistan; blood groups; allelic frequencies